Biology curriculums from the tanzimat reform to today* - Keçeci Kurt, Songül; Kurt, Murat (Journal of Turkish Science Education, 2015)
This study aims to analyze the contents of the courses related to biology education in primary and secondary education institutions and to introduce the related developments and transformations by comparing the period of change and curriculums of those courses from Ottoman Empire from the Tanzimat reform to today. Our study is based on document analysis. As a result of the current study, it is seen that biology curriculum has been given as not an individual course but within an integrated understanding which includes the subjects like nature, agriculture, medicine and geology and information which should be known by a student in daily life during the modernization period of Ottoman Empire as a result of current study. Developments in biology were reflected even partially to curriculum but lack of supporting materials of the course and the fact that courses were always given theoretically and not supported by laboratory and equipment stand out as most important deficiencies. Program for primary schools were handled mainly until 1950s and biology instruction programs were developed in the following years and scientific developments were tried to be followed within these programs in the republic period. A constructivist approach has been adopted and instruction programs have been developed within a cyclical and integrated approach after 2000s.
Keywords: Ottoman Empire; Biology Education; Curriculum